Quality Analysis of Intelligence Structure Test 2000 Revision (IST 2000R) Items in Indonesian - Medianta Tarigan; Fadillah Fadillah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2022)
This study aimed to test the quality of item analysis in the Indonesian IST 2000R using the Item Response Theory (IRT) method and participants comprising 1780 students aged 16-20. IRT 3PL analysis and DIF examination showed that the Indonesian IST 2000R had good item quality, with an improvement in IST 70. The discriminatory power parameter (ɑ) of the verbal category items was high. Furthermore, the difficulty level parameter (b) indicated that more than 50% of the items on the IST 2000R are in the average category. In the guessing probability parameter (c), 8 of 9 subtests showed that more than 50% of the items are in a low category. Overall, the Indonesian IST 2000R has a small gender bias because all subtests obtained more than 60% in category A.